Rehabilitation healthcare professionals’ perceptions of professional responsibility: a focus group study in Italy - Da Ros, Alessandra; Tozzo, Pamela; Caenazzo, Luciana (Acta Biomedica Atenei Parmensis, 2021)
BACKGROUND AND AIM OF THE WORK: Law no. 24/17 has updated the Italian legislation regarding healthcare professional responsibility. In practice, all eight groups of healthcare professionals have well defined areas of activity and responsibility. The aim of this research is to investigate how rehabilitation healthcare professionals perceive responsibility in the professional life. METHODS: a qualitative pilot study was conducted using a focus group consisting of rehabilitation professionals enrolled in the Master’s Degree program in Rehabilitation Sciences at the University of Padova. RESULTS: the analysis (performed at micro, meso and macro-level) highlighted that respondents perceived professional responsibility as a dilemma, because it is identified as a continuous balancing between external and internal pressures regarding professional competence, professional autonomy, teamwork, and social matters. CONCLUSIONS: rehabilitation professionals seem to experience a great deal of dilemmas because they felt that their responsibility was a constant challenge of weighing pros and cons. Rehabilitation professionals need a genuine autonomy recognition at every level of their practice to better cope with the professional responsibility on a daily basis. Responsibility has to be continuously and effectively implemented in all its aspects throughout the care pathway as to allow rehabilitation professionals to provide quality care to all patients. This analysis was useful for highlighting the emerging issues that need to be addressed in everyday practice.